2018
DOI: 10.1038/s41564-017-0092-4
|View full text |Cite
|
Sign up to set email alerts
|

AXL promotes Zika virus infection in astrocytes by antagonizing type I interferon signalling

Abstract: Zika virus (ZIKV) is associated with neonatal microcephaly and Guillain-Barré syndrome. While progress has been made in understanding the causal link between ZIKV infection and microcephaly, the life cycle and pathogenesis of ZIKV are less well understood. In particular, there are conflicting reports on the role of AXL, a TAM family kinase receptor that was initially described as the entry receptor for ZIKV. Here, we show that while genetic ablation of AXL protected primary human astrocytes and astrocytoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 50 publications
5
139
2
Order By: Relevance
“…Phosphatidylserine incorporation into the virion envelope allows engagement of TAM (Tyro3, Axl and Mer) receptors to promote flavivirus entry and inhibit antiviral signaling via SOCS1 (suppressor of cytokine signaling 1) induction. (80, 81) Additionally, flavivirus non-structural (NS) proteins and subgenomic flavivirus RNA (sfRNA) can directly interfere with host antiviral signaling pathways to suppress immunity. (8288) For ZIKV, the viral proteins NS1, NS2A, and NS4B have been demonstrated to antagonize the innate immune response at the level of IKKε/TBK1 (Inhibitor of kappa B kinase epsilon/TANK-binding kinase 1) activation(87, 88); whereas, NS5 has been shown to act downstream by binding IRF3 (interferon regulatory factor 3, Fig.…”
Section: How Zikv Escapes the Immune Response And Emerging Viruses Wimentioning
confidence: 99%
“…Phosphatidylserine incorporation into the virion envelope allows engagement of TAM (Tyro3, Axl and Mer) receptors to promote flavivirus entry and inhibit antiviral signaling via SOCS1 (suppressor of cytokine signaling 1) induction. (80, 81) Additionally, flavivirus non-structural (NS) proteins and subgenomic flavivirus RNA (sfRNA) can directly interfere with host antiviral signaling pathways to suppress immunity. (8288) For ZIKV, the viral proteins NS1, NS2A, and NS4B have been demonstrated to antagonize the innate immune response at the level of IKKε/TBK1 (Inhibitor of kappa B kinase epsilon/TANK-binding kinase 1) activation(87, 88); whereas, NS5 has been shown to act downstream by binding IRF3 (interferon regulatory factor 3, Fig.…”
Section: How Zikv Escapes the Immune Response And Emerging Viruses Wimentioning
confidence: 99%
“…In vitro studies with blocking antibodies and siRNA showed that during ZIKV infection of human epithelial cells, AXL and TIM‐1 are greatly responsible for viral entry. Although it has been demonstrated that GAS6 is important for ZIKV invasion of astrocytes in vitro, neither its role in vivo nor whether it exerts any suppressive activity has been addressed so far. High TAM receptors expression, along with GAS6 or PROS1, can mediate the viral entry of ZIKV, DENV, and vaccinia virus (VACV) .…”
Section: Phosphatidyl Serine Receptorsmentioning
confidence: 99%
“…Researchers have begun to study glial cells. White matter astrocytes have been found to be key responders to viral infection, and ZIKV can infect astrocytes . For JEV, microglia and astrocytes, especially the primary cell types, are the more important effector cell types …”
Section: Nervous System Target Cells Infected By Flavivirusesmentioning
confidence: 99%
“…By antagonizing postreceptor intracellular signalling of IFN, along with activation of SOCS3 expression and protein tyrosine phosphatase activity in human astrocytes, p21‐activated kinase 4 (PAK4) may regulate the JEV‐mediated inflammatory response through the mitogen‐activated protein kinase (MAPK) and NF‐κB/AP‐1 signalling pathways (Figure ) . AXL regulates the expression of SOCS1 in a STAT1/STAT2‐dependent manner, promoting ZIKV infection in human astrocytes . Thus, it appears that flaviviruses not only antagonize the host IFN antiviral response but also utilize intracellular signalling mechanisms to support their pathogenesis.…”
Section: Possible Mechanisms Underlying Flavivirus‐induced Neuronal Lmentioning
confidence: 99%